2022
DOI: 10.1075/impact.51
|View full text |Cite
|
Sign up to set email alerts
|

English Rock and Pop Performances

Abstract: This book addresses the phenomenon of non-American rock and pop singers emulating an Americanized singing style for performance purposes. By taking a novel approach to this pop cultural trend and drawing attention to the audience, British and American students’ perceptions of English rock and pop performances were elicited. Interviews guided by various music clips were conducted and analyzed through a detailed qualitative content analysis. The interviewees' responses provide important insights into social mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…These registers are in the public mind and represent styles of music or cultural and social styles (Agha 2003). However, while it is true that the indexicality of linguistic phenomena in musical genres is evident, music styles change over time and regenerate; this was found by Trudgill (1980Trudgill ( , 1983 in early studies and is also being observed by researchers in British pop and rock today (Jansen 2022).…”
Section: Stylization and Indexicality In Music Genresmentioning
confidence: 93%
See 1 more Smart Citation
“…These registers are in the public mind and represent styles of music or cultural and social styles (Agha 2003). However, while it is true that the indexicality of linguistic phenomena in musical genres is evident, music styles change over time and regenerate; this was found by Trudgill (1980Trudgill ( , 1983 in early studies and is also being observed by researchers in British pop and rock today (Jansen 2022).…”
Section: Stylization and Indexicality In Music Genresmentioning
confidence: 93%
“…Rosalía is a bilingual speaker of Catalan and S speaks Spanish, she uses phonetic phenomena specific to the Spanish o ern peninsular and, in addition, linguistic characteristics from Catalan ish such as the palatalization of /-l/ at the end of a word, the voicing of word, which is pronounced as [-t] (verdad "true" as [beɾˈð̞ a t]) or the so some speakers, who pronounce this sound as [z], e.g., in los amigos "f os] (Garachana 2018;Villena-Ponsoda 2022;Poch Oliver 2019;Rius-Esc royo 2004, 2021, 1995García Mouton 2007;Vila-Pujol 2007) a] or abanico ("fan") [ava"niko]. 11 We have also noticed examples of articulatory reinforcement of the group [st] with an affricate pronunciation [hts], which is increasingly frequent, especially in western Andalusia (Ruch and Peters 2016;Ruch 2008;Vida Castro 2015, 2022Moya Corral 2007). In studies of traditional flamenco and flamenco fusion this variant also appears in younger generations, and Rosalía continues this trend in her songs.…”
Section: Introductionmentioning
confidence: 99%